2007
DOI: 10.1088/0022-3727/40/12/020
|View full text |Cite
|
Sign up to set email alerts
|

Growth studies of (2 2 0), (2 0 0) and (1 1 1) oriented MgO films on Si (0 0 1) without buffer layer

Abstract: Selective growth of single-oriented (2 2 0), (2 0 0) and (1 1 1) MgO films on Si (1 0 0) substrates without buffer layers were obtained with a single crystal MgO target by pulsed laser deposition. All the films are very smooth and free of droplets, especially the surface of (2 2 0) and (2 0 0) oriented MgO films which are atomic-scale smooth. High resolution transmission electron microscopy was used to analyse the interfaces between MgO and Si under various conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Recently it has been reported that MgO(111) films grown on Si(100) surfaces by PLD have surfaces with an average roughness (R a ) as large as 4.9 nm at a film thickness of 75 nm, while the R a of (110) and (100) MgO film surfaces prepared similarly are 0.24 and 0.58 nm, respectively. 15) Such a large divergence in the surface roughness is consistent with the strong instability of the MgO(111) plane. Compared with the roughness of those MgO(111) films, the surface roughness in the present study is very small.…”
mentioning
confidence: 57%
“…Recently it has been reported that MgO(111) films grown on Si(100) surfaces by PLD have surfaces with an average roughness (R a ) as large as 4.9 nm at a film thickness of 75 nm, while the R a of (110) and (100) MgO film surfaces prepared similarly are 0.24 and 0.58 nm, respectively. 15) Such a large divergence in the surface roughness is consistent with the strong instability of the MgO(111) plane. Compared with the roughness of those MgO(111) films, the surface roughness in the present study is very small.…”
mentioning
confidence: 57%
“…[12][13][14] Methods such as laser ablation and magnetron sputtering are more commonly applied as the excess energy involved helps establishing epitaxial correlations. [15][16][17][18][19][20][21] On the other hand, epitaxial growth of MgO on GaAs with e-beam evaporation is well documented in literature [22][23][24] due to much better lattice matching ͑−0.7% ͒. In this letter, we demonstrate the epitaxial growth of thin ͑100͒-MgO films on top of ͑100͒-Si substrates.…”
mentioning
confidence: 79%
“…Al 2 O 3 thin films have also been used as a buffer layer in order to improve the optical properties [7] and in various types of microelectronic devices as a dielectric, diffusion and/or tunnelling barrier [8][9][10]. There are few experimental studies on the structure and properties of MgO, MgAl 2 O 4 and Al 2 O 3 thin films deposited on Si or SiO 2 by different techniques [11][12][13][14][15]. In general, the MgO films were reported to have a crystalline structure with different orientations depending on the substrate temperature [11,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…There are few experimental studies on the structure and properties of MgO, MgAl 2 O 4 and Al 2 O 3 thin films deposited on Si or SiO 2 by different techniques [11][12][13][14][15]. In general, the MgO films were reported to have a crystalline structure with different orientations depending on the substrate temperature [11,13,15]. The deposited MgAl 2 O 4 , and Al 2 O 3 films were characterized by an amorphous structure [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%